'Mulheres no volante - você trabalha ou só dirige?': uma análise das relações de trabalho por aplicativo no contexto da precarização - Ramos, Noézia Maria (2020)
This study aimed to investigate the experience of women who accept a flexible work as a driver for a Smartphone application, mediated by digital platforms, in the city of São Paulo. In recent years, labor relationships have undergone countless transformations, moving away from the traditional model of employment with formal contracts and giving way to informality, outsourcing, as well as flexible jobs on a platform, by demand and by apps, the focus of search. Such changes directly impacted Brazilian labor occupations, generating underemployment and unemployed labor. In 2019, in Brazil, year ended with 12.4 million unemployed, 53.8% of whom were women. In this context, the opportunity arises to work as a driver for an application, in a new configuration of jobs, based on a contract of partners and self-entrepreneurs, with flexible working hours regarding the needs of each one with the proposal of freedom at work and decision power. Thus, the object of this study is the work intermediated by applications, with a focus on women performing the occupation of drivers. This research is a qualitative approach, exploratory in nature, based on the interpretive paradigm, in the theoretical perspective of social constructionism, having inductive study as a method and grounded theory as a research strategy. Data collection and analysis, conducted in three steps, through 30 in-depth interviews, followed the initial, focused, selective and axial coding process, recursively, according to the guidelines by Charmaz (2009). The empirical data found in this research evidenced the financial issue as the main motivation for adopting work via Smartphone applications, followed by the feeling of empowerment, for freedom and autonomy, the desire for new experiences, and the escape from the existential emptiness after retirement. The dynamics of this type of work are exhausting, leading to more than 10 hours a day without resting and around four hours of sleep a night. The applications adopt dynamic pricing policies, prizes based on the number of runs or the financial values reached, also sending race calls before the driver completes the current trip. There is a recurring discourse of happiness and satisfaction with this type of work that contradicts the reports of daily experiences involving exploration, social isolation with constant lack of interaction with friends, frequency of physical pain (spine, knees, wrists, shoulders, and hips). There are also frequent signs of psychological illness, including cases of drivers who abandoned this model of work and are no longer able to drive at all, due to panic and anxiety crises caused by lack of security in dangerous areas, like slums, runs without monitoring and with access to company support by email only. Although there have been some improvements, the female drivers continue to blindly racing, with total ignorance of the destinations and the serious fact that the applications accept registration from consumers without photo identification and with payment in cash. In this way, this research contributes to the theme through a theoretical-empirical model of the dynamics of the daily life of application drivers, which is outlined by a process of uneasy work relationships. The model demonstrates the influences that the social and professional scenario has so that women feel attracted to know the new work model that presents itself as totally adequate to their needs of flexibility. However, divergent feelings can be generate in those women in the situation in which they find themselves, regarding the centrality and importance of the work: on the one hand, satisfaction and a sense of belonging, on the other, the resilience to endure difficulties due to the believe that “success equals sacrifice”. However, the results also pointed to a small but existing behavior of non-acceptance of the work context in this process, which is promising in the clashes, but leads to the withdrawal of some, either due to illnesses or the perception and rejection of a precarious and exploitative scenario.